The Political Skills of the Deans and its relationship to Collegiate Interpersonal Relationship - FACTORA, MAGNOLIA L. (International Journal of Psychosocial Rehabilitation, 2020)
This paper ascertained the political skills employed by the deans and how these are assessed by both the deans and the faculty. Eventually, a comparison of the assessment was made. There were 365 respondents in this study who come from 42 colleges university-wide. The quantitative method was utilized in this study. Specifically, however, its methodology was qualitative by nature since it made use of descriptive correlation. The descriptive method was used considering that the study ascertains the profile of the college deans and the political skills used. On the other hand, the correlational part involves the investigation of significant difference on the political skills of College Deans as assessed by the teachers and College Deans themselves; the significant difference in the political skills of the College Deans according to their profile variables. Results revealed that the college deans are said to be politically skilled as shown by high degree level. Using their political skills, the college deans are able to understand their subordinates when in the workplace and facilitate the said skill to influence subordinates that they may act in ways geared towards the enhancement of one’s personal objectives, eventually leading to the realization of organizational objectives. Significantly, college deans allow their subordinates to adjust their behavior in varying situations in order to draw desired feedback naturally. They also easily adapt their subordinates’ behavior to a wide are of influence in diverse contexts to achieve personal and college goals. In short, they get along with their subordinates and ultimately they get the job done in their colleges. Significantly, the study also concludes that interpersonal skill influences to a great extent the political skill of the college deans. In other words, having good interpersonal skills allows them to have higher political skill. This happens considering that interpersonal skill forms a critical dimension of political skill. It is also concluded that age and the number of faculty supervised are factors that influence interpersonal skill. They possess high political skill and interpersonal skill which are essential competencies for an effective and productive organization. The researcher recommends that the deans must sustain their level of political skill and interpersonal skill as they are important and relevant to the realization of their colleges’ goals and objectives. Further, the deans must utilize their level political skill and interpersonal skill in managing their subordinates, and linking with other internal and external linkages as they are beneficial to personal and organizational interests.